Factors associated with HIV testing among black Africans in Britain. Issue 6 (2nd December 2005) - Burns, F; Fenton, K A; Morison, L; Mercer, C; Erens, B; Field, J; Copas, A J; Wellings, K; Johnson, A M
Abstract : Objective: To describe the factors associated with HIV testing among heterosexual black Africans aged 16–44 years living in Britain. Design: We analysed data from the second British National Survey of Sexual Attitudes and Lifestyles (Natsal 2000)—a stratified national probability sample survey conducted between 1999–2001. Data from Natsal's main and ethnic minority boost (EMB) samples were analysed. Multivariate analysis was performed using complex survey functions to account for the clustered, stratified, and differential selection probabilities inherent within the survey. Results: A total of 385 (216 women and 169 men) black African respondents were included in the study. 44.0% women and 36.4% men reported ever having had an HIV test. In univariate analysis, HIV testing was associated with being born abroad (OR 3.63), having a new partner(s) from abroad in past 5 years (OR 2.88), and attending a GUM clinic (OR 3.27) among men; and educational attainment (OR 3.50), perception of "not very much" personal risk of HIV (OR 2.75), and attending a GUM clinic (OR 2.91) among women. After adjusting for potential confounders, an increased likelihood of HIV testing was associated with being in the United Kingdom less than 5 years relative to being UK born (adjusted OR 9.49), and ever attending a GUM clinic (adj OR 5.53), for men; and educational attainment (adj OR 4.13), and low perception of HIV risk (adj OR 2.77) for women. Conclusions: Black Africans appear to have relatively high rates of HIV testing reflecting, at least partially, awareness of risk behaviours and potential exposure to HIV. Nevertheless, there remains substantial potential for health gain and innovative approaches are required to further increase timely HIV testing.